Pengaruh Service Quality dan User Experience Terhadap Kepuasan Pelanggan (Studi Kasus Perumahan Givency One) - Panjaitan, Tabita; Tarigan, Eka Dewi Setia; Siregar, Dahrul (Mahesa Research Center, 2024)
The aim of this research is to determine the influence of Service Quality and User Experience on Customer Satisfaction (Case Study of Givency One Housing) both directly and indirectly. This research approach is associative. The population was 797 Givency One Housing Customers and the sample was 89 Givency One Housing Customers. Data collection techniques in this research used interview techniques, documentation studies, observations and questionnaires. The data analysis technique in this research uses Multiple Linear Regression Analysis Test, Hypothesis Test (t Test and F Test), and Coefficient of Determination. Data processing in this research used the SPSS (Statistical Package for the Social Sciences) software program version 29.00.